Geophysics and Thermodynamics at South Pole Lake Indicate Stability and a Regionally Thawed Bed. Issue 2 (27th January 2022) - Hills, Benjamin H.; Christianson, Knut; Hoffman, Andrew O.; Fudge, T. J.; Holschuh, Nicholas; Kahle, Emma C.; Conway, Howard; Christian, John E.; Horlings, Annika N.; O'Connor, Gemma K.; Steig, Eric J.
Abstract: Subglacial lakes require a thawed bed either now or in the past; thus, their presence and stability have implications for current and past basal conditions, ice dynamics, and climate. Here, we present the most extensive geophysical exploration to date of a subglacial lake near the geographic South Pole, including radar‐imaged stratigraphy, surface velocities, and englacial vertical velocities. We use a 1.5‐dimensional temperature model, optimized with our geophysical data set and nearby temperature measurements, to estimate past basal‐melt rates. The ice geometry, reflected bed‐echo power, surface and vertical velocities, and temperature model indicate that the ice‐bed interface is regionally thawed, contradicting prior studies. Together with an earlier active‐source seismic study, which showed a 32‐m deep lake underlain by 150 m of sediment, our results suggest that the lake has been thermodynamically stable through at least the last 120, 000 years and possibly much longer, making it a promising prospective site for sediment coring. Plain Language Summary: There are hundreds of subglacial lakes under the Antarctic Ice Sheet. The presence of those lakes requires sufficient heat, sourced either from the Earth's interior or from ice motion. One subglacial lake near the South Pole was previously considered a conundrum since nearby temperature measurements are cold, possibly indicating that the ice should be frozen to the surface below it. Here, we use radar and velocity measurements to better understand the ice‐sheet geometry, ice motion, and the nature of the underlying bed. We find that the lake is currently filled to within 2 m of its maximum capacity and that the entire surveyed area likely has a thawed bed. We then use nearby measurements of ice temperature and historical climate data from the South Pole Ice Core to calculate the past temperatures of the ice. These calculations indicate a thawed bed. We suggest that the lake has been thermally stable for at least the last 120, 000 years and possibly much longer. A prior study showed that the lake is underlain by 150 m of sediment, making it a candidate for sediment coring. Key Points: South Pole Lake is constrained to a 50 km 2 area, 15 km from the geographic South Pole Surface strain rates and vertical velocity profiles indicate a consistently thawed ice‐sheet bed within the surveyed area Temperature modeling suggests the lake has been thermodynamically stable for at least 120, 000 years